Grammatical subject of research articles: What novice writers can learn from professional writers in writing introduction? - Refnaldi, Refnaldi; Irawan, Andi Muhammad; Setiawan, Slamet; Ovalina, Sisri (Indonesian Journal of Applied Linguistics, 2024)
Grammatical subjects are critical as they warrant text coherence and assist in reader’s understanding of the text. They are of particular importance in a research article introduction to set up the study’s context and relevance within the wider academic discourse. This research aims to disclose what novice writers can learn from professional writers in using Grammatical Subjects (GS). It compared GS realizations and functions in Research Article Introductions (RAIs) employed by both professional and novice writers published in applied linguistic-related Journals. One hundred introduction sections from ten journals were purposely selected. 50 of them were authored by professional writers while the other 50 by novice writers. All of these sections were then examined with the use of Gosden's (1993) analytical framework. Findings revealed that both professional and novice writers employed all types of grammatical subjects. These types encompassed discourse participant, interactive participant, discourse event or process, macro and micro discourse entities, hypothesized viewpoint, and empty real-world theme. Nevertheless, the results also highlighted noticeable differences concerning the realizations of participant viewpoint, interactive discourse entity, empty discourse theme, objective viewpoint, hypothesized entity, empty H and O themes, mental process, real-world entity, and real-world event or process. These findings could help novice writers, especially non-native novice writers, navigate the use of grammatical subjects and become aware of their functions and linguistic features to establish coherent ideas in writing a research article introduction section.